ECO-FRIENDLY MANAGEMENT OF BIO-WASTES BY USING EARTHWORM, EISENIA FOETIDA. - MORE, B.C.; PATOLE, S.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The domestic solid wastes (bio-wastes) collected by municipality workers containing recyclable and compostable organic matter. With rapid growth of urbanization, the generation of municipal solid mastes has increased several folds during last few decades. Disposal of such solid wastes can be done by few methods viz., land tilling, incineration, recycling, conversion into biogas. disposal into water reservoirs and composting. Management of such wastes by using earthworm is one of the best recycling technique which will manage wastes and also improve the quality of the products. The present study aims to find out eco-friendly management of bio-wastes like vegetable wastes. kitchen wastes, saw dust and ground nut shell etc by using earthworm. Eisenia The results showed that significantly increased in macronutrients i.e. N, P and K along with other soil parameters. Appreciable amount of NPK are recorded from vermibed groups containing vegetable and kitchen wastes than saw dust and ground nut shell groups over the control groups. On other hand. except lime, Mn and Cu; all other micronutrients like organic carbon. Na. Mg, S. Fe, Ca and Zn were found to be significantly increased in all groups. The results suggest that management of bio-wastes by using vermicomposting technique is superior and helped in production of nutrient rich bio-fertilizer than using other methods of disposal.